Advanced Accounting, Volume I / Advanced Accounting Problems, Book I (Book). - Cannon, Arthur M.; Theiss, Edwin L. (The Accounting Review, 1952)
Reviews the books "Advanced Accounting," vol. 1, by George Hills Newlove and S. Paul Garner and "Advanced Accounting Problems," by George Hills Newlove and S. Paul Garner.